Africa and the West : a documentary history, Volume 1 (From the slave trade to conquest, 1441-1905) - Worger, William H.; Clark, Nancy L.; Alpers, Edward A. (Oxford ; New York : Oxford University Press, 2010)
Africa and the West presents a fascinating array of primary sources to engage readers in the history of Africa's long and troubled relationship with the West. Many of the sources have not previously appeared in print, or in books readily available to students. Volume 1 covers two major topics: the Atlantic slave trade and the European conquest. It details the beginnings of the slave trade, slavery as a business, the experiences of slaves, and the effect of abolitionism on the trade, using such documents as a letter from a sixteenth-century African king to the king of Portugal calling for a more regulated slave trade, and the nineteenth-century testimony of a South African slave accused of treason. The volume also covers the early nineteenth-century considerations of the costs and benefits of colonization, the development of conquest as the century progressed, with special attention to technology, legislation, empire, religion, racism, and violence, through such unusual documents as Cecil Rhodes's will and a chart of the costs of African animals exported to Western zoos. -- Back cover.
Volume 1. From the slave trade to conquest, 1441-1905 -- Volume 2. From colonialism to independence, 1875 to the present.
First ed. entered under title.
Includes bibliographical references and indexes.
Keywords: Slave trade -- History -- Sources; Esclaves -- Commerce -- Histoire -- Sources; History of Africa; International relations; Slave trade; Africa, Sub-Saharan -- Relations -- Europe -- History -- Sources; Europe -- Relations -- Africa, Sub-Saharan -- History -- Sources; Africa, Sub-Saharan -- Relations -- America -- History -- Sources; America -- Relations -- Africa, Sub-Saharan -- History -- Sources; Afrique subsaharienne -- Relations -- Europe -- Sources; Europe -- Relations -- Afrique subsaharienne -- Sources; Afrique subsaharienne -- Relations -- Amerique -- Sources; Amerique -- Relations -- Afrique subsaharienne -- Sources; Sub-Saharan Africa; America; Europe; History; Sources; Sources (form)